2010
DOI: 10.1093/tropej/fmq091
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Magnesium Sulphate and Sildenafil in the Treatment of the Newborns with Persistent Pulmonary Hypertension: A Randomized Controlled Trial

Abstract: The aim of this prospective, randomized and controlled study was to compare the clinical efficacy of intravenous magnesium sulfate (MgSO₄) and oral sildenafil therapies with persistent pulmonary hypertension of the newborn. A total of 34 infants in the MgSO₄ group and 31 infants in the sildenafil group completed the study. The time to reach the adequate clinical response [defined as oxygen index (OI) level of <15, a pulmonary artery pressure of < 20 mmHg) was significantly shorter in the sildenafil group (p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
37
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 18 publications
12
37
4
Order By: Relevance
“…These agents have been used successfully in treating PPHN in neonates with and without CDH [44,45]. The effects of treatment may be best addressed by repeated cardiac evaluation [46].…”
Section: Resultsmentioning
confidence: 99%
“…These agents have been used successfully in treating PPHN in neonates with and without CDH [44,45]. The effects of treatment may be best addressed by repeated cardiac evaluation [46].…”
Section: Resultsmentioning
confidence: 99%
“…significant improvement of patients' oxygenation parameters were noted at 72 hours which was comparable with other studies. [10][11][12] Ulsa et al 13 in a recent randomized clinical trial also showed that MgSO 4 was effective in the improvement of oxygenation in PPHN. Marked improvement in partial pressure oxygen at 6 hours and maximum improvement at 24 hours were found by Chandran et al 11 .…”
Section: Resultsmentioning
confidence: 93%
“…Recent RCTs conducted in resource-limiting settings and Cochrane review showed steady improvement in oxygenation after first dose of oral sildenafil with significant reduction in mortality [48][49][50]. Similarly, intravenous sildenafil has shown to improve oxygenation without causing systemic hypotension [51].…”
Section: Sildenafilmentioning
confidence: 99%